Innovation, E-Commerce, and Business Performance in Consumer-Packaged Goods Companies - Cahyono, Danang; Arief, Mts; Furinto, Asnan; Tjhin, Viany Utami (Migration Letters, 2024)
The success of the business is dependent on its performance, which in turn reveals how much money the business makes. Examining the relationship between organisational agility and innovation capabilities is the primary objective of this research, and distribution strategy transformation affect firm business performance mediated by e-commerce business adoption. The approach utilized in this study was quantitative approach. After data collection is complete, SEM-PLS analysis is performed. The findings demonstrated that (1) a company’s bottom line was positively affected by increased organizational agility, innovation capacity, and distribution strategy transformation, and (2) e-commerce adoption moderated the connection between these three factors.